2018
DOI: 10.1101/321398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial virulence against an oceanic bloom-forming phytoplankter is mediated by algal DMSP

Abstract: Emiliania huxleyi is a bloom forming microalga that impacts the global sulfur cycle by producing large amounts of dimethylsulfoniopropionate (DMSP) and its volatile metabolic product dimethyl sulfide (DMS). Top-down regulation of E. huxleyi blooms is attributed to viruses and grazers, however, the possible involvement of algicidal bacteria in bloom demise is still elusive. We isolated from a North Atlantic E. huxleyi bloom a Roseobacter strain, Sulfitobacter D7, which exhibited algicidal effects against E. hux… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 93 publications
(86 reference statements)
7
50
0
Order By: Relevance
“…huxleyi cells appears to mirror previous studies in which cellular arrest has been observed in phytoplankton in response to bacterially derived chemical exposure 19,20,21,22,23 , as well as nutrient limitation 24,25,26 . Indeed, at the physiological level, the response of E. huxleyi to HHQ parallels phosphorus (P) limitation in phytoplankton (i.e.…”
Section: Cell Cyclesupporting
confidence: 84%
“…huxleyi cells appears to mirror previous studies in which cellular arrest has been observed in phytoplankton in response to bacterially derived chemical exposure 19,20,21,22,23 , as well as nutrient limitation 24,25,26 . Indeed, at the physiological level, the response of E. huxleyi to HHQ parallels phosphorus (P) limitation in phytoplankton (i.e.…”
Section: Cell Cyclesupporting
confidence: 84%
“…In total, there are 4 complete rRNA operons, 47 tRNAs, 3,744 protein-coding genes, and 52 pseudogenes, with all RNA genes located on the chromosome. Consistent with observation of the production of methanethiol, a metabolic by-product of DMSP, during coculturing with E. huxleyi , the chromosome encoded dmdA for demethylation of DMSP ( 2 ). In addition, we identified type I and type II secretion system genes on the chromosome and type IV genes on the plasmids p2SUD7 and p3SUD7, which may be involved in the bacterium’s interactions with the alga.…”
Section: Announcementsupporting
confidence: 84%
“…Here, we report the complete genome sequence of Sulfitobacter sp. strain D7, a Rhodobacterales bacterium that, when cocultured with E. huxleyi , causes death of the alga in a DMSP-dependent manner ( 2 ). It was isolated from the microbiome of copepods collected during a natural E. huxleyi bloom in the North Atlantic, and its cooccurrence with the alga in the water column was confirmed by quantitative PCR (qPCR) ( 2 ).…”
Section: Announcementmentioning
confidence: 99%
“…S3) suggests ample opportunities for within-guild interactions in the form of competition or mutualisms (39)(40)(41). An additional level of microbial interactions occurs in natural phycospheres between bacteria and living phytoplankton that is not represented in this synthetic system; such interactions have been shown previously to encompass both mutualistic and antagonistic relationships (39,42,43).…”
Section: Discussionmentioning
confidence: 93%